OPTIMASI WAKTU DAN BIAYA DENGAN METODE TIME COST TRADE OFF PADA PROYEK PEMBANGUNAN RUANG KELAS BARU MTSN 6 MALTENG - Launuru, Julfirawati; Leuhery, Lenora; Marantika, Meyke (Jurusan Teknik Sipil, 2024)
The construction of the new classroom construction project at MTSN 6 Malteng was intended to be the object of this study because it was based on the background that occurred in the project, namely delays. Based on secondary data obtained from the project, the Budget Plan (RAB) and Time Schedule are used as project’s duration and normal costs of the project. Then the time cost trade-off method is applied which aims to be able to reduce the duration and find out the total cost needed so that the project can reach the planned time target so as not to experience delays. After accelerating with the addition of 3 hours, it could save time by 8,33% where the project cost is reduced by around 0,21%. Meanwhile, the addition of 2 hours could save time by 6,67% where the project cost is also reduced by around 0,17%. While the optimal duration and optimal costs were known in the alternative addition of 3 hours of overtime obtained 110 working days for IDR 2,992,374,365.55. Meanwhile, in addition to 2 hours of overtime, 112 working days were obtained for IDR 2,993,479,584.03.